A general protein O‐glycosylation system within the Burkholderia cepacia complex is involved in motility and virulence. Issue 1 (5th March 2014) - Lithgow, Karen V.; Scott, Nichollas E.; Iwashkiw, Jeremy A.; Thomson, Euan L. S.; Foster, Leonard J.; Feldman, Mario F.; Dennis, Jonathan J.
Summary Bacteria of the Burkholderia cepacia complex (Bcc) are pathogens of humans, plants, and animals. Burkholderia cenocepacia is one of the most common Bcc species infecting cystic fibrosis (CF) patients and its carriage is associated with poor prognosis. In this study, we characterized a general O‐linked protein glycosylation system in B. cenocepacia K56‐2. The PglLBcO‐oligosaccharyltransferase (O‐OTase), encoded by the cloned gene bcal0960, was shown to be capable of transferring a heptasaccharide from the Campylobacter jejuni N‐glycosylation system to a Neisseria meningitides‐derived acceptor protein in an Escherichia coli background, indicating that the enzyme has relaxed specificities for both the sugar donor and protein acceptor. In B cenocepacia K56‐2, PglLBc is responsible for the glycosylation of 23 proteins involved in diverse cellular processes. Mass spectrometry analysis revealed that these proteins are modified with a trisaccharide HexNAc‐HexNAc‐Hex, which is unrelated to the O‐antigen biosynthetic process. The glycosylation sites that were identified existed within regions of low complexity, rich in serine, alanine, and proline. Disruption of bcal0960 abolished glycosylation and resulted in reduced swimming motility and attenuated virulence towards both plant and insect model organisms. This study demonstrates the first example of post‐translational modification in Bcc with implications for pathogenesis.